2022
DOI: 10.3390/polym14245470
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Applications of Green Thermoplastic and Thermosetting Nanocomposites Based on Nanolignin

Abstract: The development of bio-based materials is of great importance in the present environmental circumstances; hence, research has greatly advanced in the valorization of lignin from lignocellulosic wastes. Lignin is a natural polymer with a crosslinked structure, valuable antiradical activity, unique thermal- and UV-absorption properties, and biodegradability, which justify its use in several prospective and useful application sectors. The active functionalities of lignin promote its use as a valuable material to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 60 publications
0
1
0
Order By: Relevance
“…Traditionally, lignin has been viewed as a waste by-product of the paper and pulp industry and burned as a low-value fuel. However, in recent years, there has been growing interest in developing lignin-based materials for high-value applications, such as bioplastics, composites, and coatings [8][9][10][11]. Lignins are complex polymers consisting of various phenylpropanoid units and their structures are highly dependent on the plant source, extraction method, and processing conditions [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, lignin has been viewed as a waste by-product of the paper and pulp industry and burned as a low-value fuel. However, in recent years, there has been growing interest in developing lignin-based materials for high-value applications, such as bioplastics, composites, and coatings [8][9][10][11]. Lignins are complex polymers consisting of various phenylpropanoid units and their structures are highly dependent on the plant source, extraction method, and processing conditions [8].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, lignins are UV-absorbing polyphenols, which can improve the UV barrier of materials [12]. However, several studies showed that decreasing their particle size to the "nano" level further improved these properties, making them more suitable for nanocomposites production [8,10,11]. Given the promising properties of lignin nanoparticles (LNPs), various strategies have been proposed for their production, including solvent exchange, pH-shift, emulsion templates, and CO 2 anti-solvent techniques [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Despite this disadvantage, much work has been done to develop the full potential of lignin. Puglia et al explored the application of lignin in renewable thermoplastics, taking advantage of the many functionalities of lignin [15]. Besides, lignin can also be used in film production, which could improve the UV barrier ability and mechanical properties of the film.…”
Section: Ligninmentioning
confidence: 99%
“…Torre, Puglia, and Luzi have contributed a fascinating review paper on the preparation and applications of green thermoplastic and thermosetting nanocomposites based on nanolignin [3]. In this review article, the authors pay attention to lignin's valorization from plenty of lignocellulosic wastes.…”
mentioning
confidence: 99%